Multiobjectives design of a multirate output controller - Shen, Liang. (2008)
Named as "Multiobjectives Design of a Multirate Output Controller", we consider multirate output controllers (MROCs) and research on the robust performance under //?, Hoc as well as mixed H21 Hx specifications. As the sampled-data control system, which consists of a MROC, is a hybrid, time-varying system (periodic), we must use some norm-equivalent methods to first convert this kind of system to a time-invariant system. Among these methods, we first use the fast discretization technology to discretize the ·whole system, then use the discrete lifting to convert a MROC system to a suitable discrete-time system, in the sense that the robust index from the input signals to the output signals still remain the same.